Therapeutic Potential of Hyporesponsive CD4+ T Cells in Autoimmunity - Maggi, Jaxaira; Schafer, Carolina; Ubilla-Olguín, Gabriela; Catalán, Diego; Schinnerling, Katina; Aguillón, Juan C. (Frontiers in Immunology, 2015)
The interaction between dendritic cells (DCs) and T cells is crucial on immunity or tolerance induction. In an immature or semi-mature state, DCs induce tolerance through T cell deletion, generation of regulatory T cells and/or induction of T cell anergy. Anergy is defined as an unresponsive state that retains T cells in an “off” mode under conditions in which immune activation is undesirable. This mechanism is crucial for the control of T cells responses against self-antigens, thereby preventing autoimmunity. Tolerogenic DCs (tDCs), generated in vitro from peripheral blood monocytes of healthy donors or patients with autoimmune pathologies were shown to modulate immune responses by inducing T cell hyporesponsiveness. Animal models of autoimmune diseases confirmed the impact of T cell anergy on disease development and progression in vivo. Thus, the induction of T cell hyporesponsiveness by tDCs has become a promising immunotherapeutic strategy for the treatment of T cell-mediated autoimmune disorders. Here we review recent findings in the area and discuss the potential of anergy induction for clinical purposes.